2023
DOI: 10.1117/1.oe.62.7.075102
|View full text |Cite
|
Sign up to set email alerts
|

Optical design of a freeform, gradient-index, head-mounted display

Abstract: .I present the results of an optical design study into the performance benefits of non-rotationally symmetric “freeform” gradient-index (GRIN) media on a pupil-relay head-mounted display. A range of design variants are presented based on freeform-GRIN lenses consisting of ternary base-material combinations that are enabled by recent developments in additive manufacture. The optical performance of these designs is compared to homogeneous solutions comprising combinations of spherical, aspheric, toric, and freef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…And although results were promising, no designs were fabricated and further research has not been published since 2017. The potential for multi-material three-dimensional (3D) ink-jet printing has also motivated the recent work of Boyd, where multi-material F-GRIN have been investigated for the first time [31,32]. The present work seeks to continue prior multi-material GRIN research by developing theory, design intuition, showing the added utility of a fourth base material, and highlighting a previously unexplored effect for multimaterial GRIN.…”
Section: Multi-materials Gradient-index Opticsmentioning
confidence: 91%
See 2 more Smart Citations
“…And although results were promising, no designs were fabricated and further research has not been published since 2017. The potential for multi-material three-dimensional (3D) ink-jet printing has also motivated the recent work of Boyd, where multi-material F-GRIN have been investigated for the first time [31,32]. The present work seeks to continue prior multi-material GRIN research by developing theory, design intuition, showing the added utility of a fourth base material, and highlighting a previously unexplored effect for multimaterial GRIN.…”
Section: Multi-materials Gradient-index Opticsmentioning
confidence: 91%
“…Numerous design studies have shown the utility of refractive index distributions that vary along two independent spatial dimensions [44][45][46][47]. And more recently, their usefulness in multi-material F-GRIN systems has also been demonstrated [31,32]. The following sections reexamine the first-order properties when axial dependence is introduced and investigate more complicated design forms where the refractive index varies in two independent spatial dimensions.…”
Section: Axially-dependent Multi-materials Grin; or Multi-materials F...mentioning
confidence: 97%
See 1 more Smart Citation